(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
In this study genetic diversity and interspecific relationships of 11 Allium L. species from Khorassan province of Iran including 32 accessions were investigated by inter simple sequence repeat (ISSR) markers. Nine ISSR primers produced a total of 80 polymorphic markers and revealed high polymorphism among the studied species. The average gene diversity, effective number of alleles and Shannons information index were 0.2, 1.28 and 0.3, respectively. Allium kuhsorkhense exhibited the greatest level of variation (He: 0.18), whereas A. stipitatum demonstrated the lowest level of variability (He: 0.05). UPGMA (Unweighted Pair Group Method with Arithmetic mean) analysis showed that Allium accessions have a similarity range of 0.60 to 0.95. Allium scapriscapum composed the most distant group in the dendrogram. The clustered groups of Allium species clearly reflect the recent taxonomic concept of the genus at the subgenus and section levels. The present study showed that the ISSR technique is an effective molecular approach for analyzing genetic diversity and relationship in Allium species. Bangladesh J. Plant Taxon. 22(2): 67-75, 2015 (December)